Critical role of miR877-5p in proliferation and adhesion of triple negative breast cancer - Grinpelc, Agustina (2023)
Breast cancer (BC) is the leading cause of cancer death in women. Triple negative breast cancer (TNBC) is the molecular subtype that is known for having a poor prognosis and limited therapeutic options compared to other subtypes of BC. MiRNAs are small non-coding RNAs that regulate gene expression. Aberrant expression of miRNAs in body tissues and fluids are linked to pathologies such as BC.